2 PFO closure is superior to medical therapy for cryptogenic stroke: a meta-analysis of randomised controlled trials. (June 2018) - Ahmad, Yousif; Howard, James; Arnold, Ahran; Shun-Shin, Matthew; Cook, Christopher; Malik, Iqbal; Mayet, Jamil; Francis, Darrel; Sen, Sayan
Abstract : Background: The efficacy of patent foramen ovale (PFO) closure for cryptogenic stroke has been controversial. We undertook a meta-analysis of randomised controlled trials (RCTs) comparing device closure with medical therapy to prevent recurrent stroke for patients with PFO. Method s and results : We systematically identified all RCTs comparing device closure to medical therapy for cryptogenic stroke in patients with PFO. The primary efficacy endpoint was recurrent stroke, analysed on an intention-to-treat basis. The primary safety endpoint was new onset atrial fibrillation (AF). 5 studies (3440 patients) were included. 1829 patients were randomised to device closure and 1611 to medical therapy. PFO closure was superior to medical therapy for prevention of stroke (HR 0.32 (0.13–0.82), p=0.018, I 2 =73.4%). The risk of AF was significantly increased with device closure (RR 4.54, 95% CI 2.17 to 9.48, p<0.001, heterogeneity I 2 =22.9%). Conclusion: In patients with cryptogenic stroke and PFO, device closure is superior to medical therapy for the prevention of further stroke.